2012
DOI: 10.2190/il.20.3.b
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Growth and Transformation as Outcomes of Perinatal Loss

Abstract: Perinatal loss in its many forms results in profound grief and distress for women, their partners, and families. The possibility of personal growth in the aftermath of perinatal loss has been suggested through early research; however, systematic research on posttraumatic growth after perinatal loss has not been well-developed. Posttraumatic growth is positive psychological change as a result of confronting a challenging life experience. After a short description of perinatal loss, this article presents the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…This suggests a form of post-traumatic growth by which, over time, people learn to cope with and grow from their experience of grief (see [49]).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a form of post-traumatic growth by which, over time, people learn to cope with and grow from their experience of grief (see [49]).…”
Section: Discussionmentioning
confidence: 99%
“…This concept refers to the process of transformation, which results in the occurrence of positive changes in self-perception, relationships with others and philosophy of life (Tedeschi & Calhoun, 1996, 2004. Transformation associated with bereavement has been conceptualized as a form of learning, which shapes assumptions and expectations about the world, rendering the bereaved person more inclusive, open, reflective and able to change (Black & Wright, 2012;Mezirow, 2003). It indicates that the shattered personal life resulting from such a negative experience as loss of a child provides the opportunity to make a transition towards growth.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have indicated the occurrence of positive changes among parents who have lost a child (Black & Wright, 2012;Büchi et al, 2007Büchi et al, , 2009Engelkemeyer & Marwitt, 2008;Lichtental, Currier, Neimeyer, & Keesee 2010;Martincekova & Klatt, 2016;Pan, Liu, Li, & Kwok, 2016;Polatinsky & Esprey, 2000;Thomadaki, 2012;Znoj, 2006). Calhoun, Tedeschi, Cann, and Hanks (2010b) stress that unexpected death, such as the death of a child, is less consistent with most assumptive world views than natural death, and as a result may lead to greater growth.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, bereavement may induce spiritual change: as a life crisis it can challenge one's assumptions about human existence [ 7 ]. Although the death of a loved one may incur great distress and impair one's spirituality [ 8 ], it may also trigger psychospiritual transformation and facilitate spiritual growth [ 9 ]. Therefore, researchers should pay more attention to ways of improving the spiritual well-being of the bereaved.…”
Section: Introductionmentioning
confidence: 99%